Tantangan dan Solusi Manajemen Persuratan di Era Digital - Nindya Azzahrah; Aidatul Fauziah; T. Darmansah; Elsa Elitia Hasibuan; Soleh Parlindungan (Journal Innovation In Education, 2024)
In the digital era, mail management faces significant challenges related to data security, operational efficiency and technological adaptation. The transformation from manual to digital systems demands fundamental changes in the way organizations manage incoming and outgoing mail information. Key challenges include the risk of data leaks, cyber threats, the need for reliable technology infrastructure, and resistance to change among staff. In addition, difficulties in integrating the various digital platforms used by organizations often hinder process automation and efficiency.